Sleep Time Estimated by an Actigraphy Watch Correlates With CSF Tau in Cognitively Unimpaired Elders: The Modulatory Role of APOE - López-García, Sara; Lage, Carmen; Pozueta, Ana; García-Martínez, María; Kazimierczak, Martha; Fernández-Rodríguez, Andrea; Bravo, María; Reyes-González, Luis; Irure, Juan; López-Hoyos, Marcos; Rodríguez-Rodríguez, Eloy; Sánchez-Juan, Pascual (Frontiers in Aging Neuroscience, 2021)
There is increasing evidence of the relationship between sleep and neurodegeneration, but this knowledge is not incorporated into clinical practice yet. We aimed to test whether a basic sleep parameter, as total sleep estimated by actigraphy for one week, was a valid predictor of CSF Alzheimer’s Disease core biomarkers (amyloid-β-42 and -40, phosphorylated-tau-181, and total-tau) in elderly individuals, considering possible confounders and effect modifiers, particularly the APOE ɛ4 allele. One hundred and twenty-seven cognitively unimpaired volunteers enrolled in the Valdecilla Study for Memory and Brain Ageing participated in this study. Seventy percent of the participants were women with a mean age of 65.5 years. After adjustment for covariates, reduced sleep time significantly predicted higher t-tau and p-tau. This association was mainly due to the APOE ɛ4 carriers. Our findings suggest that total sleep time, estimated by an actigraphy watch, is an early biomarker of tau pathology and that APOE modulates this relationship. The main limitation of this study is the limited validation of the actigraphy technology used. Sleep monitoring with wearables may be a useful and inexpensive screening test to detect early neurodegenerative changes.